2019
DOI: 10.1016/j.ejpoleco.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable fiscal strategies under changing demographics

Abstract: * This version of the article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the publisher's final version AKA Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In contrast, Hughes Hallett et al [98] contend that fiscal sustainability is not a matter of long-term debt but is an issue of changes in taxes and spending in transition. In a more recent study, Hughes Hallett et al [99] contend that even deteriorating population parameters, a relatively benign steady state is possible. Nevertheless, they emphasize that probably it will achieve with some fiscal and financial breakdowns along the way.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, Hughes Hallett et al [98] contend that fiscal sustainability is not a matter of long-term debt but is an issue of changes in taxes and spending in transition. In a more recent study, Hughes Hallett et al [99] contend that even deteriorating population parameters, a relatively benign steady state is possible. Nevertheless, they emphasize that probably it will achieve with some fiscal and financial breakdowns along the way.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A key question is what a standard macroeconomic model would say about the behavior of an economy following demographic shocks, such as lower fertility rates and increases in longevity. Recent work of ours- Bokan et al (2016) and Hughes Hallett et al (2019)-has established that a new steady state exists despite deteriorating demographics. Also, our research has shown that it is a benign steady state in terms of economic growth and the optimal level of public debt.…”
Section: Introductionmentioning
confidence: 98%
“…In this section we outline the building blocks of the model while referring to Bokan et al (2016) andHughes Hallett et al (2019) for further detail.…”
mentioning
confidence: 99%
“…The works of many scientists are devoted to the study of the impact of demographic trends on economic development (Gasparenienea and Remeikienea, 2016). Docquier et al (2019) explore demographic trends and human development; Strulik (1999) studies the development of demography and economic cycles; Hallett et al (2019) research sustainable fiscal strategies under changing demographics; and Volodymyr Gumeniuk explores the impact of demographic factors on the financial stability of tourism enterprises (Gumeniuk, 2015). O'Sullivan (2020) argues that stabilization of the population is needed to ensure stable economic development of the state.…”
Section: Introductionmentioning
confidence: 99%